The effect of nutritional education based on health belief model on nutritional knowledge, Health Belief Model constructs, and dietary intake in hemodialysis patients - Narjes Nooriani; Vida Mohammadi; Awat Feizi; Hossein Shahnazi; Gholamreza Askari; Elham Ramezanzade (Wolters Kluwer Medknow Publications, 2019)
Background: Based on the results of many studies on the relationship between nutritional status and clinical implications in dialysis patients, malnutrition is one of the most important factors associated with mortality in these patients. The current study examined the effect of nutritional education based on Health Belief Model (HBM) on nutritional knowledge, HBM constructs, and dietary intake in Hemodialysis (HD) patients. Materials and Methods: One-hundred chronic HD patients entered to this randomized clinical trial in 2017 in Iran; 41 in control group and 45 in intervention group completed the study. Demographic data and four 24-h recalls were collected. To evaluate the nutritional knowledge and HBM constructs, a researcher-made questionnaire was used. Patients were evaluated before, immediately after, and 3 months after intervention. Eight 1-h education sessions in 4 weeks were considered for intervention group. Independent samples t-test, Chi-square test, and repeated measures ANOVA were used to analyze the data. Results: Repeated measures ANOVA test showed significant increases in scores of the nutritional knowledge test, perceived susceptibility, perceived severity, perceived barriers (p = < 0.001), perceived benefits (p = 0.010), and self-efficacy (p = 0.019) after the study in the intervention group. There were no significant differences between two groups in energy, protein, High Biologic Value (HBV) protein, carbohydrate, fat, cholesterol, fiber, vitamin B2, B3, B6, B12, E, calcium, phosphorus, and potassium intake. Conclusions: It seems that education based on HBM can improve nutritional knowledge but in order to influence on dietary intake, longer interventions that are more comprehensive are needed.